2010
DOI: 10.1103/physrevd.82.012002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of higher-order Laguerre-Gauss mode interferometry

Abstract: The compatibility of higher-order Laguerre-Gauss (LG) modes with interferometric technologies commonly used in gravitational wave detectors is investigated. In this paper we present the first experimental results concerning the performance of the LG33 mode in optical resonators. We show that the Pound-Drever-Hall error signal for a LG33 mode in a linear optical resonator is identical to that of the more commonly used LG00 mode, and demonstrate the feedback control of the resonator with a LG33 mode. We succeede… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…LG As already verified in other experiments [14,15], the Pound-Drever-Hall error signals of the Fabry-Pérot cavities for the Gaussian and LG 33 modes are the same. The error signal for the LG 33 mode is shown in Fig.…”
Section: Gaussiansupporting
confidence: 61%
See 1 more Smart Citation
“…LG As already verified in other experiments [14,15], the Pound-Drever-Hall error signals of the Fabry-Pérot cavities for the Gaussian and LG 33 modes are the same. The error signal for the LG 33 mode is shown in Fig.…”
Section: Gaussiansupporting
confidence: 61%
“…Up to now, two table-top experiments have demonstrated the generation of a high purity LG 33 mode for GW detection using a diffractive element, either a liquidcrystal-on-silicon spatial-light modulator [14] or a fusedsilica plate [15], in combination with a linear mode-cleaner cavity. Two further experiments have investigated this technique at scales closer to a real gravitational wave detector by increasing either the laser power or the length of the optical system: the former [16] was focused on the LG 33 high-power generation by a diffractive phase plate, while the goal of the latter [17] was to inject an LG 33 mode into a suspended 10-m-long Fabry-Pérot cavity in vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…Future effort will be directed toward the construction of a new family of optical modes which can reduce the thermal noise impact while simultaneously being robust against mirror imperfections. Here we show that the contrast defects defined in equations (15) and (14) are equivalent in the limit of small perturbations. We denote the input and output field for the two cavities (X and Y) as |in X , |out X , |in Y , |out Y .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the practical advantages associated with the use of spherical mirrors, experimental testing of LG 3,3 modes has begun. It has thus far been demonstrated that these modes can be generated with high efficiency and resonated in tabletop cavities with small mirrors [14,15]. An unpleasant property of higher-order LG modes is that each LG p,l mode is 2p + |l| + 1-fold degenerate, the LG 3,3 mode being 10-fold degenerate.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the detection rate of binary neutron star in spiral systems -which are considered the most promising astrophysical sources for a first GW detection -could be enhanced by about a factor of 2 or more 16 at the cost of a minimal amount of modifications in the design of second-generation interferometers currently under construction 10,11 . The proposed method combines techniques and expertise developed in diverse areas of physics and optics such as the generation of high stability, low noise single mode laser beams 23 , the use of spatial light modulators and diffractive optical elements for the manipulation of the spatial profiles of light beams 18,22,24,25,26 , and the use of advanced techniques for the sensing, control and stabilization of resonant optical cavities 27 aiming at a further purification and stabilization of the laser light. This method has been successfully demonstrated in the laboratory experiments, exported for tests in large-scale prototype interferometers 20 , and for generating LG modes at high laser powers up to 80 W…”
Section: Introductionmentioning
confidence: 99%